Implementación de un modelo de simulación de una unidad de recepción con ecualización para aplicaciones de canales de transmisión de datos a alta velocidad - Netzer-Hernández, José Daniel (Instituto Tecnológico de Costa Rica, 2017)
Due to the constant increase of information traffic in electronics systems, in recent years new technologies have evolved rapid pace. This fact demands the design of new methods of digital communications that allow to increase the speed of processing. The increase of speed, combined with the limitations of the bandwidth of the communication channel, increase the effects of Intersymbol Interference (ISI). It is necessary to implement powerful equalization schemes at the receiver. To compensate the impairment effects, it is necessary the Decision Feedback Equalizer (DFE) represents one of the most used equalization techniques in the industry. [19] Due to the difficulty of simulations and prediction of the behavior of the highspeed data transmission channels, with the different equalization schemes, the Costa Rica Institute of Technology, in cooperation with the Institute of Electromagnetic Theory of the Technical University of Hamburg, are developing an investigation. This project aims to implement a simulation that characterize the behavior of this type of equalizer on highspeed channels, analyzing the mean squared error criterion for the estimation of the optimal coefficients for the equalizer. Based on estimates and simulations implemented with Advanced Design System (ADS) software, the proposed models were successfully validated with respect to other models from the literature, comparing their impact on different configurations at high data rates.
Proyecto de graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2017.
Keywords: Sistemas; Diseño; ADS; DFE; ISI; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics